Nest site selection during the second breeding attempt in Japanese tits (Parus minor): effects of nest site characteristics - Xudong Li; Jiangping Yu; Li Zhang; Dake Yin; Keqin Zhang; Mingju E; Haitao Wang (Scientific Reports)
Abstract Numerous investigations focusing on nest site selection among multiple-brooded bird species have revealed a common trend: breeders frequently return to their first nest sites for another brood during the same breeding season. This behavior suggests a strong preference for familiar locations, which may offer advantages such as increased safety, resource availability, and the efficiency of parental care. However, there were also instances where breeders moved to a new nest site. Habitat changes linked to nest-switching in birds that breed multiple times in a season have not been thoroughly explored. This research aimed to determine whether Japanese tits (Parus minor), who are facultatively double-brooded, alter the features of their nest sites due to changes in the surrounding environment during their second breeding attempt. We compared nest site features of the Japanese tit’s nest boxes used for the first brood, those used for the second brood, and control nest boxes (which were unoccupied and located in the same forest patch as the nest boxes for the second brood during the corresponding year). The findings indicated that, when compared to control nest boxes, the nest boxes occupied by Japanese tits for the second brood exhibited shorter shrub height, smaller average DBH of the surrounding trees, yet higher nest height and increased density of shrubs. In comparison to nest boxes used for the first brood, those used for the second brood exhibited lower shrub height, increased shrub density and higher nest height. Our study suggested that nest site selection for the second brood by tits might be influenced by unique site characteristics, which could be linked to factors such as food accessibility or predator avoidance.